High Prevalence of Nutritional Risk Among Pulmonary Patients Living on the Tibetan Plateau - Quncuo, Chilie; Liang, Ying; Li, Qiuyu; She, Xiaoli; Cuo, Bian Ma; Qiongda, Bianba; ChuTso, Meilang; Sun, Yongchang (Frontiers in Nutrition, 2022)
Background Nutritional risk is associated with adverse clinical outcomes and is more prevalent among pulmonology patients than among patients in other departments. High-altitude environments can affect patients with chronic respiratory diseases, but evidence of the prevalence of nutritional risk among hospitalized patients with respiratory diseases in high-altitude areas is limited. This study aimed to investigate the nutritional risk and status of inpatients with different major respiratory diagnoses permanently living on the Tibetan Plateau (≥3,000 m above sea level). Methods In this cross-sectional study, we consecutively recruited inpatients admitted to the Department of Respiratory and Critical Care Medicine at the Tibet Autonomous Region People's Hospital of Lhasa between November 2020 and May 2021. We used the Nutrition Risk Screening (NRS) 2002 tool to assess nutritional risk among these patients. An NRS 2002 score ≥3 points indicates nutritional risk; a score ≥5 indicates high nutritional risk. According to NRS-2002 scores, patients were divided into three groups (NRS-2002 0–2, 3–4, and ≥5). The differences in age, sex, major respiratory diagnoses, comorbidities, body mass index, and laboratory findings among the groups were analyzed. Results A total of 289 eligible Tibetan patients were enrolled in the study, and 46.1% (133/246) of them were at nutritional risk (NRS-2002 score ≥3). Twenty-one (7.3%) patients were at high nutritional risk (NRS-2002 score ≥5). The proportions of patients at nutritional risk were relatively high among patients with lung cancer (58.8%), interstitial lung disease (58.3%), pulmonary embolism (52.9%), and tuberculosis (50.0%). Laboratory findings showed that patients with NRS-2002 scores of 3–4 and ≥5 had lower red blood cell counts, serum albumin and hemoglobin levels, and higher C-reactive protein (CRP) levels than those with NRS-2002 scores < 3. Conclusion The prevalence of nutritional risk was high among pulmonology department inpatients permanently living on the Tibetan Plateau. Patients with lung cancer, interstitial lung disease, pulmonary embolism or tuberculosis were more likely to have nutritional risk than patients with other diagnoses. The nutritional risk of inpatients in the respiratory department in the plateau area should not be ignored, and patients at high nutritional risk should receive timely intervention.